A Hybrid OSM–BIM Framework for Construction Management System - Ghasemi Poor Sabet, Pejman (Curtin University, 2020)
In this study, an in-depth evaluation was conducted to determine the influences of interactions between off-site manufacturing (OSM) and building information modelling (BIM) on overall project performance. Structural equation modelling method was adopted to examine the complex relationships among research variables based on survey data. The results showed that a systematic adoption of the interactions as a mediator between OSM and BIM, significantly enhanced the overall project performance as measured by key productivity indicators.